Demography of Indonesia's Ethnicity - Arifin, Evi Nurvidya; Pramono, Agus, 1955-; Handayani, Nur Budi; Hasbullah, M. Sairi (Book collections on Project MUSE., 2015)
Indonesia, the largest country in Southeast Asia, has as its national motto "Unity in Diversity." In 2010, Indonesia stood as the world's fourth most populous country after China, India and the United States, with 237.6 million people. This archipelagic country contributed 3.5 per cent to the world's population in the same year. The country's demographic and political transitions have resulted in an emerging need to better understand the ethnic composition of Indonesia.This book aims to contribute to that need. It is a demographic study on ethnicity, mostly relying on the tabulation provided by the BPS (Badan Pusat Statistik; Statistics-Indonesia) based on the complete data set of the 2010 population census. The information on ethnicity was collected for 236,728,379 individuals, a huge data set.The book has four objectives: To produce a new comprehensive classification of ethnic groups to better capture the rich diversity of ethnicity in Indonesia; to report on the ethnic composition in Indonesia and in each of the thirty three provinces using the new classification; to evaluate the dynamics of the fifteen largest ethnic groups in Indonesia during 2000-2010; and to examine the religions and languages of each of the fifteen largest ethnic groups.